The use of a cellular automaton land use model as a tool for urban planning - Agostinho, Joaquim Manuel Mocito. (2007)
Thesis (M.A.)--Memorial University of Newfoundland, 2008. Geography Includes bibliographical references (leaves (164-171) A constrained Cellular Automata (CA) based model of the land use dynamics of Dublin, Ireland, is used as a platform to evaluate planning strategies at both metropolitan and regional scales. In particular, the New Urbanism movement advocates a variety of strategies from zoning to urban growth boundaries in order to reduce sprawl, increase densities, and encourage mixed use development. These strategies are implemented in the CA land use dynamics model and the resulting land use patterns are evaluated and compared with results in the absence of planning constraints, using spatial metrics such as Total Urban Edge and fractal dimensions. Some apparently powerful planning measures such as the imposition of an urban growth boundary are found to have a limited effect.